Implementing machine learning into industrial plant energy supervision - Martin, John Sebastian (My University, 2021)
Machine learning is a concept in which a machine can learn from its past experiences. The machine learning trend is rising in popularity, and this is the reason this method has been chosen for this thesis. The purpose of this thesis is to analyze how well machine learning analyzes energy usage in a zinc plant. This thesis work has been split into two pieces as the electrowinning works separately and the roaster and sulphuric acid plant work together. The roaster and sulphuric acid plant are connected and therefore the power changes affect the whole process. There are thousands of signals from the plant so to make the analyses as good as possible only the essential ones were chosen. The electrowinning data was analyzed with Random Forest and Roaster and sulphury acid data was analyzed with Neural Network. During this thesis multiple programs have been exploited such as SQL was used to extract the data, Microsoft excel was for editing data and the analyses were executed with Orange data mining program as it is a good method to test and visualize data. The results show that the tests are successful and how the different categories can be found with the help of machine learning. And that when watching what the machine learning methods priorities as important factors, it is very different from what we consider as vital information. However, when simulating classes that were not successful there was not as much success as when the simulations were done with the imaginary situations and the values did not match what a real event would look like. Koneoppiminen on konsepti, jossa kone pystyy oppimaan aikaisemmista tapahtumista. Koneoppimisien kiinnostavuus on kasvussa ja tämä on yksi syy, miksi juuri tämä työ valittiin. Tämän tutkielman tarkoituksena on analysoida, miten hyvin koneoppiminen pystyy analysoimaan energian käyttöä sinkin tuotannossa. Tämä työ on jaettu kahteen osaan, koska elektrolyysin energian-käyttö ei suoraan vaikuta pasuttamon ja rikkihappotehtaan energia kulutukseen. Pasutus ja rikkihappotehdas ovat prosessikokonaisuus, joten energia muutokset pasutuksessa vaikkutavat happotehtaaseen. Prosessissa on tuhansia signaaleja ja jotta saisimme analysoinnista mahdollisimman hyvän, oli olennaista valita vain tärkeimmät signaalit. Elektrolyysi osassa käytettiin Random Forest menetelmää ja pasuttamoon ja happotehtaan analysointiin käytettiin neuroverkko menetelmää. Tämän työn aikana käytettiin useita ohjelmia kuten SQL:ää käytettiin datan poimintaan, Microsoft Exceliä käytettiin data muokkaamiseen ja Orange data mining ohjelmaa käytettiin analysointiin ja visualisointiin. Tulokset osoittavat, että testit onnistuivat ja näyttävät myös, miten koneoppi pystyy luokittelemaan eri tyyppistä dataa. Myös, siten miten koneoppiminen priorisoi signaaleja, tämä riippuu todella paljon siitä, miten me katsomme signaalien painoarvoa. Mutta kuin simuloimme vääränlaisia luokkia niin tulokset eivät olleet niin hyviä kuten olimme toivoneet, ja tämä riippuu todennäköisesti siitä että simuloitavat arvot eivät ole saman tyyppisiä kuten miltä arvot olisivat todellisessa vikatilanteessa.
Keywords: machine learning; artificial intelligence; energy technology; fi=Automaatio- ja tietotekniikka|en=Automation and Computer Science|; fi=Tietotekniikan koulutusohjelma (DI)|en=Degree Programme in Information Technology|